Combined Effects of Molybdenum and Cooling Rate on Microstructure and Tribo-Mechanical Properties of Ductile Iron - Kaymak, Kubra; Gecu, Ridvan; Celik, Kubra; Keyvankli, Ahmet Bugra (SPRINGER INT PUBL AG, 2025)
EN-GJS-400-15 (GGG40) ductile irons were alloyed with Mo (0, 0.25, 0.5, 1, and 2 wt.%), and ten variants were produced by casting in Y-block sand molds with section thicknesses of 12.5 mm and 25 mm. Microstructural characterization was conducted using FESEM, EDX, optical microscopy, and Clemex image analysis. Mechanical and tribological properties were evaluated through hardness, tensile, and ball-on-disk wear tests. The addition of Mo promoted carbide formation at grain boundaries-predominantly M7C3 in the thinner sections and M23C6 in the thicker ones-along with an increased pearlite content in the matrix. These changes enhanced hardness, ultimate tensile strength, and yield strength, though at the expense of ductility. Under an 18 N load against an Al2O3 counterface, the 2 wt.% Mo alloy exhibited approximately a 65% reduction in wear rate compared to the unalloyed baseline. Surface analysis revealed adhesive, abrasive, and oxidative wear mechanisms. Overall, the 2 wt.% Mo alloy demonstrated the most favorable balance of mechanical strength and wear resistance.
Keywords: molybdenum; ductile iron; molybdenum carbide; wear; mechanical behavior; CAST-IRON; ALLOYING ELEMENTS; WEAR-RESISTANCE; NODULE COUNT; SLIDING WEAR; BEHAVIOR; SOLIDIFICATION; TRANSFORMATION; SEGREGATION; MORPHOLOGY; Metallurgy & Metallurgical Engineering